Covid-19 And Chinese Reaction To African Migrants - Adeola Adebisi; Saliu Akeem (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
Coronovairus, also known as COVID-19 is an infectious disease ravaging lives across the world. This paper is an examination of Chinese relationship with African migrants during COVID-19 pandemic. It examines the relationship between Chinese and Africans amid the lockdown and as well investigates Chinese-African co-existence before the outbreak of the virus. The study derives its data majorly from documentaries which are subjected to internal and external criticisms for authorization. It was realized in this study that despite the invitation extended to Chinese doctors to assist Nigeria, and bilateral relations between China and African countries, African residents in China were maltreated and denied privileges. The implications of these on African-Chinese relations are increased in incoherent interconnectedness and fragile Chinese investors in African countries which are partly, some of the salient reasons for setback for emerging co-existence and economic ties between African countries and China after independence.